Digital-Based Learning In English Language Classrooms: A Systematic Literature Review Of Technologies And Research Trends (2020-2026) - Anisa Puspadewi; Witri Sawalia; Gina Raisah; Handini Aprillia Ros; Debby Farhani Alwy; Elyza Martiarini (International journal of technology and education research, 2026)
The development of digital technology has brought significant changes to English language learning and encouraged the emergence of various technology-based learning innovations. This study aims to analyze the development of digital-based learning in English classrooms during the period 2020–2026, covering research trends, types of technology used, benefits, and implementation challenges. The study used the Systematic Literature Review (SLR) method by adapting the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, which include identification, screening, eligibility, and inclusion stages. Data were obtained from various scientific databases, namely Google Scholar, Scopus, ScienceDirect, ERIC, and SpringerLink. A total of 25 articles that met the inclusion criteria were analyzed using thematic analysis techniques. The results show that digital-based learning has experienced rapid development, especially after the COVID-19 pandemic. The most dominant technologies used are Learning Management Systems (LMS), Artificial Intelligence (AI), social media, mobile learning applications, and gamification. Digital technology contributes to increasing learning motivation, student engagement, access to authentic learning resources, English language skills, and learning independence. Its implementation still faces various challenges, such as limited internet access, low digital literacy, inadequate teacher training, and dependence on technology. This study concludes that digital-based learning has great potential to support more adaptive, personalized, and student-centered English learning in the digital age.